Prevalence and Characterization of Staphylococcus aureus Isolated From Pasteurized Milk in China - Dai, Jingsha; Wu, Shi; Huang, Jiahui; Wu, Qingping; Zhang, Feng; Zhang, Jumei; Wang, Juan; Ding, Yu; Zhang, Shuhong; Yang, Xiaojuan; Lei, Tao; Xue, Liang; et al. (Frontiers in Microbiology, 2019)
Staphylococcus aureus is one of the most important food-borne pathogens globally. It produces various toxins and invasive enzymes and can be found in numerous food products. Milk is an important source of staphylococcal food poisoning. After pasteurization, this microorganism or its enterotoxins might still remain in pasteurized milk. Therefore, this study was to investigates the contamination of S. aureus in 258 pasteurized milk from 39 cities of China. The prevalence and levels of S. aureus in these samples as well as antibiotic susceptibility profiles, virulence genes, biofilm formation and biofilm related genes, spa typing and MLST were used to determine the characterization among the isolates. It was found 3.9% of samples were detected S. aureus in 8 of 39 cities in China.The contaminated level were not very excessive which showed the MPN values of the most positive samples (9/10) were less than 1 MPN/g. All pasteurized milk-related S. aureus isolates have ability to produce biofilm and harbored icaA, icaD, eno, clfA, clfB, fnbA, fnbB, fib genes, other biofilm related genes icaC were showed in 91.7% of isolates and cna gene were showed in 50%, except bap gene which were free in all isolates. The antibiotic susceptibility test showed that all isolates were resistant or intermediate-resistant to different concentrations of the antibiotics. Furthermore, 75.0% of the isolates were resistant to three or more antibiotic classes, which indicated multidrug resistance. The isolates had virulence potential, which showed 66.7% (8/12) of the isolates carried one or more virulence-associated genes. Molecular typing by MLST and spa typing enabled classification of these isolates into a total of 11 sequence types (STs) and spa types, which indicated high genetic diversity. Most of these types were related to various clinical S. aureus infections. Thus, the findings of this study reflect the potential risk of S. aureus infection in China. Our study also provides comprehensive analysis of the prevalence of S. aureus in pasteurized milk and helps ensure more accurate treatment of human infection with effective antibiotics.